GABA-B Receptor Encephalitis Triggered by Enterovirus Encephalitis in a Patient With Small Cell Lung Cancer: A Case Report. Issue 4 (July 2020) - Kim, Seong Hoon; Kim, Woojun
Abstract : Introduction: Encephalitis with gamma-aminobutyric acid (GABA)-B receptor antibodies (GABA-B receptor encephalitis) is known to have underlying neoplastic condition in half of the cases; however, there could be an additional event that could work as a trigger factor. Here, we report a patient with GABA-B receptor encephalitis associated with small cell lung cancer, which was probably triggered by enterovirus encephalitis. Case Report: A 53-year-old man was admitted for a seizure, following fever and headache for 3 days. Status epilepticus developed on the following day. Brain magnetic resonance imaging (MRI) was normal. Cerebrospinal fluid (CSF) study revealed lymphocyte-dominant pleocytosis, and enterovirus was detected by polymerase chain reaction test in CSF later. The patient recovered after 2 weeks of treatment. Another 2 weeks later, he showed confusion and seizure without fever. Follow-up CSF study revealed no abnormalities; however, MRI showed a lesion with vasogenic edema on the right posterior hippocampus. GABA-B receptor antibodies were found in the serum and CSF. The chest computed tomography revealed a mass on his right upper lung, which was confirmed as a small cell lung cancer. GABA-B receptor encephalitis associated with small cell lung cancer was diagnosed, and intravenous immunoglobulin and methylprednisolone were infused. Following treatment, seizures and delirium stopped, and the patient recovered to a near normal state. Follow-up MRI performed 2 months later showed that the hippocampal lesion had disappeared. Conclusion: In cases of infectious encephalitis with an atypical recurrent course, the possibility of newly onset autoimmune encephalitis should be considered.